5x+2x(x-3) =4x-3(x+1) solve and check
Answers
Answered by
0
Answer:
PLEASE MAKE ME BRAINLIST AND GIVE ME
Attachments:
![](https://hi-static.z-dn.net/files/d71/d2e70ee69bee91bfa6f1a06952f354c4.jpg)
![](https://hi-static.z-dn.net/files/d94/dfc945c2bca4a49d887a68d7c65f4785.jpg)
Answered by
0
Answer:
= − 2 0
Step-by-step explanation:
Distribute
5 + 2 ( − 3 ) = 4 − 3 ( + 1 )
5 + 2 2 − 6 = 4 − 3 ( + 1 )
Combine like terms
5 + 2 2 − 6 = 4 − 3 ( + 1 )
− + 2 2 = 4 − 3 ( + 1 )
Rearrange terms
− + 2 2 = 4 − 3 ( + 1 )
2 2 − = 4 − 3 ( + 1 )
= − 2 0
Similar questions